Vibração de plantas de pimenta (capsicum sp) para produção de frutos e sementes em ambiente protegido - Freitas, Pâmela Gomes Nakada [UNESP] (2014)
The pollinators produce the vibration of flowers to release pollen to fertilize the eggs cells for seed formation and fruit development. In this sense, it is aimed to verify the effect of the vibration of plants in the production of american pepper protected with open and closed sides cultivation. The experiment was conducted at the Experimental Farm of UNESP/FCA located in the city of São Manuel-SP. There were six treatments in a split plot design, with two instalments, one with vibration and other without vibration of the plants in subplots the three cultivars (Dirce, Dínamo and Doce Comprida). The plants were vibrated shooking on the wire where it attaches the tutor (bamboo cane) by hand for about 5 seconds, twice a day. The design was a randomized block design with three replications. The same experiment was conducted in two environments: with and without closing the sides. The characteristics were evaluated: weight and number of total and marketable fruit (no visible defects) per plant, percentage of marketable fruits; mass, diameter and fruit length , weight and number of seeds per fruit , and plant height. Fruit production was much higher in the environment with closed sides with 24 marketable fruits per plant while in open areas there were seven. The vibration of plants of american peppers did not affect yield, length, diameter and average fruit weight. Just cultivating Doce Comprida gave higher seed production per fruit in the open environment in relation to confinement, in the absence of plant vibration, averaging 259 and 126 seeds per fruit, respectively. The vibration indoors benefited cultivar Doce Comprida.